The cowboy cookie challenge - Wilde, Lori (Wilde, Lori. Twilight, Texas novel., 2022)
"Roan Sullivan is the naswer to Jazzy Walker's prayers. The doting single dad is a whiz at campfire cooking, so who better to help her win this year's annual cookie challenge? With his help, Jazzy is sure she can finally take first prize right out of the grasping hands of Andi Browning, the gal who stole her fiance right from under her nose. A widower with a four-year-old daughter, Roan tells himself there are a million reasons not to help Jazzy. She's too king, too optimistic, and could do so much better than hitching up with a curmudgeon like him. But every time she draws near, he can't help but wonder if he could open his heart and love again. As Christmas draws close, the magic of Twilight starts to weave its spell...and soon it's not just the competition that's heating up, it's the hot sizzle between Roan and Jazzy." --Page [4] of cover.